A Study on Problems in Promotion of Women Rural Entrepreneurs in Kanniyakumari District (International Journal of Food and Nutritional Sciences, 2022)
Rural entrepreneurship plays a vital role in driving economic growth, fostering innovation, and promoting inclusive development in rural areas. However, its promotion faces numerous challenges that hinder its full potential. This abstract provides an overview of the key problems in the promotion of rural entrepreneurship and outlines the need for further research and policy interventions to address these challenges effectively. The abstract begins by highlighting the significance of rural entrepreneurship in fostering economic development and reducing rural-urban disparities. It then identifies and discusses several critical challenges that impede the promotion of rural entrepreneurship, including limited access to finance, inadequate infrastructure, lack of market linkages, limited technical and managerial skills, and socio-cultural barriers. These challenges are often exacerbated by the remote and resource-constrained nature of rural areas, making it difficult for aspiring entrepreneurs to establish and sustain successful businesses.